Application of new technologies for increasing fatigue characteristics of lock-on connec¬tions of compressor blades - Цыбанев, Г. В.; Налимов, Ю. С.; Кононученко, О. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the results of experimental research of influence of technology of vibration strengthening and blade root coating on cyclic strength of lock-on connection under condition of fretting corrosion